OVERVIEW OF IOT BASED WATER MANAGEMENT SYSTEM - Shamal Sanjay Kharat; Prof. Sumera Ali; Prof. Devendra L. Bhuyar (International Journal of Innovations in Engineering Research and Technology, 2021)
18% of world’s population lives in India. On the other hand the usable water availability is less as compared with the population in India. Around 4 % of world’s usable water is present in India. The water is basic need of human being. India is facing issues with uneven distribution of rainfall and on the other hand the need of water for drinking and other day to day activities is unavoidable. The available water is not used in proper amount and hence many times the water is wasted. It is also observed that, the drainage water is mixing with the sources of clean water and contaminating it. Due to improper drainage system the present clean water is also wasted. The utilisation pattern of water is varying with the region, type of crops in the farm, and the industrial utilisation. It is necessary to control the wastage of water and it is necessary to develop the disciplined water utilisation habits amongst the people. Authors have presented the IoT based water management system in this paper.